THE EFFECT OF THE USE OF MOBILE BANKING ON STUDENTS OF JAKARTA STATE UNIVERSITY - Putri Fauziyah Nur Azizah; Mardi Mardi; Santi Susanti (International Journal of Multidisciplinary Research and Literature, 2022)
This study aims to determine the effect of bank security and reputation on decisions to use mobile banking for students at the State University of Jakarta. This study uses a quantitative approach. The data in this study are primary data using a questionnaire. The population in this study were students of the Faculty of Economics, State University of Jakarta, Class of 2018. The sample selection used a purposive sampling technique. The respondents in this study were 200 students of the 2018 State University of Jakarta. The analytical method used was multiple regression analysis. The results of the study indicate that there is an influence of security on the decision to use mobile banking. In addition, there is the effect of bank reputation on the decision to use mobile banking